Pattern of pigmentation disorder in Cosmetic Dermatology Clinic H. Adam Malik General Hospital, Medan, 2012 - 2015 - Jusuf, Nelva Karmila (Journal of General - Procedural Dermatology and Venereology Indonesia, 2017)
Background: Abnormalities of pigmentation is a cosmetic problem which affects the overall appearance of an individual. Pigmentation disorder are caused by the increase (hypermelanosis) or the decrease (hypomelanosis) amount of melanin. Objective: To determine the pattern of pigmentation disorder in Cosmetic Dermatology Clinic H. Adam Malik General Hospital Medan in 2012-2015. Methods: A retrospective study using subject's medical records from the Cosmetic Dermatology Clinic H. Adam Malik General Hospital Medan in 2012 - 2015, presented descriptively. Results: In 2012 - 2015 the number of patients who visited the Cosmetic Dermatology Clinic were respectively 210, 228, 211, 142. Hypermelanosis were found respectively in 24.76%, 16.20%, 12.79%, 5.63%. Whereas hypomelanosis were found 18.10%, 9.21%, 8.53%, 8.45%. During 2012 - 2015 melasma was the most common disorder found among hypermelanosis group, followed by post inflammatory hyperpigmentation. Meanwhile vitiligo was the only diagnosis in hypomelanosis group. Each year most of the pigmentation disorder patients came from the age group 38-48 years old except in 2015. Women were more affected than men.  Conclusion: In 2012-2014, the largest proportion of pigmentation disorder were hypermelanosis, mostly melasma. In 2015, it was hypomelanosis with vitiligo as the diagnosis.